1983
DOI: 10.1007/bf01852282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on platelet aggregation: An in vitro study

Abstract: Alcohol ingestion results in the formation of circulating microaggregates in the pig. To investigate the underlying mechanism, the effects of alcohol on platelet aggregation using a Born-aggregometer, was investigated. After incubating unstirred platelet rich plasma (PRP) with moderate concentrations of alcohol (175 mmol/l) the aggregation induced by collagen was reduced. This was probably due to platelet refractoriness caused by platelet ADP release. We could also demonstrate that high concentrations of alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The present results are in concordance with earlier results from animal experiments where alcohol in similar concentrations caused a prolongation of the bleeding time, an increase in blood loss after a standardized liver resection [ 12] and platelet refractoriness in vitro [11], Impairment of human platelet function by alcohol in vitro has been demon strated recently [33,34]. The mechanism by which alcohol affects platelet function re mains unknown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results are in concordance with earlier results from animal experiments where alcohol in similar concentrations caused a prolongation of the bleeding time, an increase in blood loss after a standardized liver resection [ 12] and platelet refractoriness in vitro [11], Impairment of human platelet function by alcohol in vitro has been demon strated recently [33,34]. The mechanism by which alcohol affects platelet function re mains unknown.…”
Section: Discussionsupporting
confidence: 92%
“…One explanation is that alcohol in creases the levels of high-density lipoproteins which remove cholesterol from the walls of coronary arteries [7,8], Another possibility is that alcohol protects the heart by reducing psychological stress [9], Yet another hypothe sis is that alcohol may affect the formation of a prostaglandin that in turn affects the aggre gation of platelets [10]. This hypothesis is supported by our previous studies in vitro and in vivo in experimental animals showing impaired platelet function and hemostasis by alcohol [11,12], A possible effect of alcohol on platelets, should be of interest also for sur geons who treat victims of trauma often in jured and treated while under the influence of alcohol [13], The present study was therefore undertaken to investigate the effect of alcohol on platelet function, coagulation and fibrino lysis in healthy humans. Our data confirm that alcohol affects platelet function as dem onstrated by a prolongation of the bleeding time and impairment of platelet aggrega tion.…”
Section: Introductionmentioning
confidence: 75%
“…Such concentrations, however, exceeded previously recorded plasma levels and would be highly toxic in life [1,14]. Interestingly, in vitro addition of ethanol to platelet-rich plasma at 630-2600 mM elicited aggregation, whereas lower levels, consistent with those registered after moderate intoxication, failed to trigger a similar reaction, acting inhibitory to ADP and collagen-induced aggregation [3,6,7]. It is possible that aggregation at extremely high levels of ethanol or acetaldehyde consisted of a non-specific toxic platelet reaction.…”
Section: Discussionmentioning
confidence: 76%
“…In the present study, collagen-induced platelet aggregation (1–8 μ g/mL) was evaluated after 5 μ L of test substance solution dissolved in methanol was added to 195 μ L of whole blood. Alcohol is suggested to modify platelet functions [ 25 ]. However, in preliminary study, we confirmed in this experimental condition that there were no significant differences of the degree of collagen-induced platelet aggregation (1–8 μ g/mL) in the samples with or without methanol.…”
Section: Discussionmentioning
confidence: 99%